ARSITEKTUR BIOMORFIK PADA PERANCANGAN TAMAN FLORIKULTURA DI KOTA DENPASAR - I Kadek Mahardika; Ida Bagus Idedhyana; Ayu Putu Utari Parthami Lestari (Jurnal Teknik Gradien, 2023)
The floriculture garden plays an important role in the preservation of plants, especially ornamental plants and also plays a role in overcoming the problem of global warming and contributes to the provision of urban green open spaces. The unwise exploitation of the existing biodiversity is one of the reasons for increasing greenhouse gas emissions in Indonesia. In addition, there is also a phenomenon of reduced open space in urban areas due to land conversion due to the high population growth in Indonesia. This is in accordance with the current condition of the city of Denpasar which has become an urban city with the most populous population in the province of Bali. This phenomenon makes the area of ​​Denpasar City Public green open space less than the ideal standard. On the other hand, there are still many types of ornamental plants in Indonesia that have not been conserved. Thus, it is necessary to procure a Floriculture Park in Denpasar City to overcome the problem of the number of ornamental plants that have not been conserved, global warming that occurs, and the reduction of green open space in urban areas. This design also aims as a recreational and educational facility. The basic concepts used are recreational, conservation and educational. While the chosen design theme is a biomorphic architectural theme with sustainable forms, structures and materials. The design method used is data collection techniques in the form of library research, observation and comparative studies, as well as data processing methods, namely analysis, synthesis and transformation methods. The results of the design of the Floriculture Park in Denpasar City are explained into three principles of biomorphic architecture. The first principle is the principle of form, namely the form of mass based on ecology and metaphor of natural forms. The second principle is the principle of structure and material, its application is the use of structures with organic shapes, while in terms of materials the application is by selecting natural (local) materials and materials that support a curvilinear shape. The third principle is the principle of sustainability, the application of which is to maximize the use of natural energy into buildings.